Enhancing Listening Skills Through Media Use in Learning for Seventh Grade Students of Junior High School - Fimela, Jonathan; Pierre Nduwingam (CV. Mitkom Indotama, 2024)
Teachers find it difficult to impart listening skills to students learning English as a second language.Therefore, the goal of this study is to help students become better listeners. By utilizing audio-visual materials, this classroom action research (PTK) aims to help students' listening abilities.By utilizing audio-visual materials, this study seeks to enhance pupils' listening abilities. The study's participants were seventh-grade SMP SWASTA PGRI KOTA KUPANG. The planning, observation, action, and reflection cycles were used to perform this study. In order to encourage student participation in the classroom, collaborative learning techniques were also used. The findings demonstrated that audio-visual media could enhance the learning outcomes of listening courses